Effect of chloroform on insect succession and carcass decomposition in peat swamp forest - Khoo, Pau Seng (Universiti Malaysia Sarawak, (UNIMAS), 2012)
Six fresh carcasses were used in this study in peat swamp forest at UNIMAS from 15th November 2011 to 2nd March 2012. The objective of this study was to compare the stages of decomposition and faunal succession between a chloroform-killed rabbit carcass and carbon dioxide-killed rabbit carcass. Two rabbits weighed approximately 500g were used in each experiment and there were three replicate in this study. Both rabbits were euthanized with different method and immediately placed in a peat swamp forest behind the Kolej Kenanga, UNIMAS. Both carcasses were visited twice per day (morning and evening). Adult insects and larvae on the carcasses were collected and later processed in the entomology laboratory. Both carcasses were completely decomposed to remain stage after five days. The species visiting the both carcasses consisted of blow flies (Chrysomya megacephala, Chrysomya rufifacies, and Hypopygiopsis violacea). The only difference noted was the number of species and the amount of adult flies were seen more in the chloroform-killed rabbit carcass.